Achieving high strength and high ductility in Al0.3CoCrNi medium-entropy alloy through multi-phase hierarchical microstructure - Sathiyamoorthi, Praveen; Park, Jeong Min; Moon, Jongun; Bae, Jae Wung; Asghari-Rad, Peyman; Zargaran, Alireza; Seop Kim, Hyoung (Materialia, 2019)
The enhancement of strength in materials by conventional strengthening mechanism is always accompanied by loss of ductility due to the reduced strain hardenability, leading to a strength–ductility trade-off. In this paper, we engineered Al0.3CoCrNi medium-entropy alloy to contain multi-phase hierarchical microstructure and demonstrated a high yield strength of ∼1 GPa, a high tensile strength of ∼1.2 GPa, with a uniform elongation and total elongation of ∼28% and ∼39%, respectively. The multi-phase hierarchical microstructure is developed by a simple processing route of cold rolling followed by annealing. The superior combination of strength and ductility is primarily attributed to the generation of back stress, high strain hardening rate, and formation of deformation twins.